miR-124 regulates the epithelial-restricted with serine box/epidermal growth factor receptor signaling axis in head and neck squamous cell carcinoma - Zhang, Manchao (Mol Cancer Ther, 2015)
Epithelial-restricted with serine box (ESX), a member of the ETS transcription factor family, is elevated and regulates epidermal growth factor receptor (EGFR) in head and neck squamous cell carcinoma (HNSCC). However, the molecular mechanisms that contribute to ESX dysregulation remains to be elucidated. In this study, in silico analysis of the 3′-untranslated region (UTR) of ESX predicted two miR-124 binding sites. Delivery of miR-124 inhibited the 3′UTR ESX-driven reporter activity by 50% (p<0.05) confirming ESX as a direct target of miR-124. Loss of miR-124 was found to a frequent event in HNSCC. miR-124 expression was significantly depleted in the primary tumor compared to matched normal tissue in 100% (12/12) of HNSCC patients; relative mean miR-124 expression of 0.01197 and 0.00118 (p<0.001, n=12) in matched normal adjacent tissue and primary HNSCC tumor, respectively. Over-expression of miR-124 decreased ESX and EGFR levels in miR-124(low)/ESX(high)/EGFR(high) SCC15 HNSCC cells and reduced cell invasion, migration, proliferation and colony formation. SCC15 cells with miR-124 restoration were less tumorigenic in vivo than miR-control SCC15 cells (70% inhibition, p<0.01). Restoration of miR-124 in SCC15 cells enhanced the anti-proliferative efficacy of the EGFR/Her2 TKIs. Furthermore, recapitulation of EGFR in miR-124 over-expressing SCC15 cells was sufficient to completely block the anti-proliferative effects of lapatinib and afatinib. Taken together, our work provides intriguing evidence that miR-124 is a novel therapeutic approach to reduce ESX/EGFR and may be a tractable strategy to enhance the response rate of HNSCC patients to current anti-EGFR/Her2 therapies.